Leakage mechanism of cation -modified BiFeO3 thin film - Jiagang Wu; John Wang; Dingquan Xiao; Jianguo Zhu (AIP Advances, 2011)
To investigate the leakage mechanisms in cation -substituted BiFeO3 (BFO) thin films, in Bi site or Fe site or both sites, Bi0.92La0.08FeO3, BiFe0.95Mn0.05O3, and Bi0.92La0.08Fe0.95Mn0.05O3 thin films were grown in situ by radio frequency magnetic sputtering on SrRuO3/SrTiO3(111) substrates, where the (111) orientation is established in all thin films. The variation in cation substitution results in different leakage behavior of BFO thin films. Space charge limited conduction and a grain boundary limited behavior are responsible for the leakage behavior of Bi0.92La0.08FeO3 and BiFe0.95Mn0.05O3 thin films in a low electric field region, respectively, while an interface-limited Fowler-Nordheim tunneling is involved in their leakage behavior in a high electric field region. In contrast, the leakage of Bi0.92La0.08Fe0.95Mn0.05O3 endures a transition from an Ohmic conduction to space charge limited conduction with increasing electric fields. The three thin films however show little temperature dependence of the leakage behavior in the temperature range investigated.